Pollen viability and stigma receptivity in sunflower (Helianthus annuus) - CH. S. LAKSHMI; K. KANAKA DURGA; R. ANKAIAH; A.R.G. RANGANATHA (Seed Research, 2026)
Pollen viability is a critical factor determining the success of sunflower seed production. Fresh pollen-grains without blending of filler material recorded maximum viability. The pollen-grains stored in refrigerator recorded higher viability (%) compared to those stored in moist earthen pots. This may be attributed to low temperature of 4°C and 75% RH prevailing in refrigerator. Storage of pollen grains in earthen pots surrounded with moist sand was adjudged as the next best treatment since their viability could be maintained through in a lower scale up to fifth day. Irrespective of filler material and storage methods, viability (%) and stigma receptivity decreased with increased age of pollen-grains.